Effect of physical development parameters and conditioning abilities on the level of motor coordination in female volleyball players in the phase of specialized basic training - Boichuk, R.; Iermakov, S.; Kovtsun, Va.; Pasichnyk, V.; Melnyk, V.; Lazarenko, M.; Troyanovsky, M.; Kovtsun, Vi. (Journal of Physical Education and Sport, 2018)
Purpose: The objective of the study was to identify the effect of physical education parameters and conditioning capabilities on the level of motor coordination manifestations in the female volleyball players at the stage of specialized basic training. Material: 20 female volleyball players aged 15 to17 participated in the study. Results: certain range of problems aggravating efficient training process of young female volleyballers has been revealed. It has been proved that the improvement of female volleyball players` motor skills is of crucial significance for proper mastering and efficient application of volleyball technique elements during competitive activities. Correlation between physical development characteristics and coordination and conditioning skills has been revealed. Average rate of negative correlation between female athletes` body length parameters and their ability to maintain dynamic equilibrium has been identified. Low and average rate correlations have been registered between the capability of immediate manifestation of spatial orientation, rhythm and body weight index. Valid interdependence of average rate between the majority of coordination readiness characteristics of female volleyballers and their speed and strength qualities has been investigated. The combined effect method for simultaneous improvement of coordinating and conditioning preparedness in 15-17 year old female volleyball players was applied in accordance with the specific knowledge about quantitative correlation between the above mentioned, all in all inconsistent, characteristics of a human being. Conclusions: in order to master the efficient volleyball technique it is obviously essential for a volleyball player to possess corresponding physical qualities and skills. Definition of correlation between coordinating skills of volleyballers and other parameters of their motor activity could enable better control of female volleyballers` physical perfection. Major somatic characteristics have minor if any effect upon general level of coordinating readiness of female volleyball players in the phase of specialized basic training.